Japan's open future an agenda for global citizenship - Haffner, John (Anthem Press, 2009)
For many decades Japan enjoyed great success with its export oriented economy and the outsourcing of its foreign policy to the United States under the US security umbrella. Its role in the world was simple, and times were good. But times have changed. With the end of the Cold War, a shrinking domestic population, global instabilities after 9/11, the financial crisis, and other seismic shifts, Japan now faces a more complicated world. In this groundbreaking and provocative discussion, three foreigners who have lived and worked in Japan, a Canadian, a Frenchman and a Spaniard, argue that Japan has much to gain by pursuing a more engaged, outward-looking, multilateral posture in its region and globally. While the country will continue to enjoy good relations with the West, the time has come for Japan to embrace its Asian heritage and future, as well as its own potential contribution to world affairs. A globally engaged, more open Japan, the authors argue, is win win win: good for Japan, good for Asia, and good for the world. If Japan is truly to become a global citizen, however, it must not only reach out more to the world, it must also admit more of the world, new ideas, people, and capital from afar, on its own soil. But is Japan, are Japanese, prepared to do so?.